Mobile edutainment AR treasure hunt application - Chong, Jia Ni (2021)
Mobile Edutainment AR Treasure Hunt is a virtual treasure hunt simulation game by implementing Augmented Reality (AR) feature into the application. Treasure hunt is being known by the public since long time ago. In western country, this game is being adopted widely in education field particularly in pre-school due to their education nature that promoting creative learning process compared to eastern country that mostly implementing practical-based learning method. Due to different education systems, the learning process in eastern country tend to be rigid and lack of interactivity causing most of the children lost their motivation to learn. Henceforth, this treasure hunt application is developed to improve the interactivity of learning through gaming in order to boost children motivation to learn as well as to conduct a favourable and interesting learning process for children. With the transformation of digital technology, treasure hunt now can be implemented virtually through mobile application platform. In this application, both “Creator” (the one creates treasure hunt) and “Player” roles can be performed in one mobile platform. The “Creator” can hide the treasures through phone camera and set clues and questions. After done with the setting, the “Creator” then can pass to the “Player” to play. Hence, through this application, user can play treasure hunt effortlessly without having to prepare clue cards and treasures then find a place to hide it which requires lots of effort. To achieve the hiding of virtual treasure into the real world through camera, AR technique is used. The AR feature in this application is implemented through Vuforia which is an AR SDK for user to bring the virtual object into a real world. Last but not least, in order to integrate 3D model, animation and audio effects for a game, Unity game engine is used with the Vuforia SDK to develop this treasure hunt application.